NIAT MENABUNG PADA BANK SYARIAH BAGI PENGELOLA UMKM MUSLIM KOTA YOGYAKARTA - Mr Sukardi (UMSurabaya Publishing, 2016)
ABSTRACT This study aims to find the factors that influence the intention of saving deposits in Islamic banks for the Muslim umbul municipal Yogyakarta. Product knowledge, religiosity and attitudes are predicted to have an effect on the intention of saving in sharia banks for the managers of SMEs Muslim city of Yogyakarta. The population in the study were the managers of Muslim SMEs Yogyakarta City, their number is not yet known. The sample of this research respondents a number of sixty two (62) people, the technique of determining the sample with cluster sampling.Data collection was done by questionnaire, each question item was measured using Likert scale. Data were analyzed by using multiple linear regression. The result shows that simultaneously there is positive and significant influence between the variable of attitude of saving, religiosity (piety), and the produck of knowledge on the intention of saving at Bank Syariah for SME manager of Yogyakarta City, with F counting 8.4661 and level of significance 0,000.Terdapat positive and significant influence variable attitudes toward the intention of saving to the Islamic Bank for the management of SMEs Muslim city of Yogyakarta with t count (0200) and the level of significance 0.063 (for 10%), there is a positive and significant influence on the variable religiosity to saving intentions with t arithmetic (0.303) and the level of significance 0.011 (for 10% and 5%), but there is no significant effect of produck knowledge on saving intention with t arithmetic (0.158) and significance level of 0.132 Keywords : product knowledge, religiosity, attitudes and intention to save sharia bank.Correspondence to : sukardi_feuad@yahoo.com ABSTRAK Kajian ini bertujuan untuk mencari faktor faktor yang mempengaruhi niat menabung pada bank syariah bagi pengelola umkm muslim kota Yogyakarta.Product knowledge, religiusitas dan sikap diprediksikan memiliki pengaruh terhadap niat menabung pada bank syariah bagi pengelola UMKM Muslim kota Yogyakarta. Populasi pada penelitian adalah para pengelola UMKM Muslim Kota Yogyakarta, jumlah mereka belum diketahui. Adapun sampel responden penelitian ini sejumlah enam puluh dua (62) orang, teknik penentuan sampelnya dengan claster sampling.Pengumpulan data dilakukan dengan kuesioner, setiap item pertanyaan diukur dengan menggunakan skala Likert.Data dianalisis dengan menggunakan regresi linier berganda. Hasilnya menunjukkan bahwa secara simultan terdapat pengaruh positif dan signifikan antara variabel sikap menabung, religiusitas (kesalehan), dan produck knowledge terhadap niat menabung pada Bank Syariah bagi pengelola UMKM Kota Yogyakarta, dengan F hitung 8.4661 dan tingkat signifikansi 0,000.Terdapat pengaruh positif dan signifikan variabel sikap terhadap niat menabung pada Bank Syariah bagi pengelola UMKM muslim kota Yogyakarta dengan t hitung (0.200) dan tingkat signifikansi 0.063 (untuk 10 %), terdapat pengaruh positif dan signifikan pada variabel religiusitas terhadap niat menabung dengan t hitung (0.303) dan tingkat signifikansi 0.011 (untuk 10 % maupun 5%), tetapi tidakterdapat pengaruh yang signifikan produck knowledge terhadap niat menabungdengan t hitung (0.158) dan tingkat signifikansi 0.132.Kata kunci : product knowledge, religiusitas, sikap dan niatmenabung bank syariah.Korespondensi : sukardi_feuad@yahoo.com